Feline panleukopenia (review) - A. M. Kiselev; S. V. Shcherbinin; T. S. Galkina (Ветеринария сегодня)
Feline panleukopenia, a disease globally known since the beginning of the last century and originally attributed to canine distemper, has expanded its range of hosts since its discovery as a result of successful infections (both natural and experimental) in mustelids, raccoons and even primates. Evolutionarily, the disease pathogen gave rise to anew infectious agent– canine parvovirus, which, despite its DNA structure, demonstrates a relatively high mutation rate and the emergence of new variants. The disease is in most cases fatal to newborn kittens and causes severe manifestations in adult cats, severely aﬀecting the vital systems of the body. The prognosis is often (up to50%) unfavorable, while the animal’s age plays a key role. Current preventive measures can ensure protection, however, vaccines are used in the absence of adequate testing on cats and dogs (for ethical reasons) and have a number of limitations in use. The persistence of the infectious agent in the environment and the growing number of stray animals allow the infectious agent to circulate unhindered in these populations, threatening the health of domestic cats and endangered felines in nature reserves and zoos. Easing of legislation for leading research centers, regulation of the number of stray animals, adequate prevention measures for target groups in animal shelters, nurseries and zoos can contribute to a signiﬁcant reduction in the circulation insusceptible populations of pathogens not only of this disease, but also of the majority of other dangerous infections, such as rabies, feline rhinotracheitis, canine distemper and others.